Neuronal Membrane Disruption Occurs Late Following Diffuse Brain Trauma in Rats and Involves a Subpopulation of NeuN Negative Cortical Neurons - Hernandez, Martina L.; Chatlos, Todd; Gorse, Karen M.; Lafrenaye, Audrey D. (Frontiers in Neurology, 2019)
The repercussions of traumatic brain injury (TBI) endure years following the initial insult and involve chronic impairments/disabilities. Studies indicate that these morbidities stem from diffuse pathologies, however, knowledge regarding TBI-mediated diffuse pathologies, and in particular, diffuse neuronal membrane disruption, is limited. Membrane disruption has been shown to occur acutely following injury, primarily within neurons, however, the progression of TBI-induced membrane disruption remains undefined. Therefore, the current study investigated this pathology over a longer temporal profile from 6h to 4w following diffuse TBI induced using the central fluid percussion injury (CFPI) model in rats. To visualize membrane disruption, animals received an intracerebroventricular infusion of tagged cell-impermeable dextran 2h prior to experimental endpoints at 6h, 1d, 3d, 1w, 2w or 4w post-CFPI. The percentage of total neurons demonstrating dextran uptake, indicative of membrane disruption, was quantified within the lateral neocortex layers V and VI from 6h-4w post-injury. We found that membrane disruption displayed a biphasic pattern, where nearly half of the neurons were membrane disrupted sub-acutely, from 6h-3d post-TBI. At 1w the membrane disrupted population was dramatically reduced to levels indistinguishable from sham controls. However, by 2w and 4w following CFPI, approximately half of the neurons analyzed displayed membrane disruption. Moreover, our data revealed that a subset of these late membrane disrupted neurons were NeuN negative (NeuN-). Correlative western blot analyses, however, revealed no difference in NeuN protein expression in the lateral neocortex at any time following injury. Furthermore, the NeuN- membrane disrupted neurons did not co-label with traditional markers of astrocytes, microglia, oligodendrocytes, or NG2 cells. Immunohistochemistry against NeuN, paired with a hematoxylin and eosin counter-stain, was performed to quantify the possibility of overall NeuN+ neuronal loss following CFPI. A NeuN- population was observed consistently in both sham and injured animals regardless of time post-injury. These data suggest that there is a consistent subpopulation of NeuN- neurons within the lateral neocortex regardless of injury and that these NeuN- neurons are potentially more vulnerable to late membrane disruption. Better understanding of membrane disruption could provide insight into the mechanisms of diffuse pathology and lead to the discovery of novel treatments for TBI.